Budd-Chiari Syndrome in a Patient With Simultaneous Diagnosis of Hepatic Sarcoidosis and Nodular Regenerative Hyperplasia. Issue 9 (September 2019) - Odah, Tarek; Al-Khazraji, Ahmed; Idriss, Rajab; Morrow, Matthew; Curry, Michael P.
Abstract : ABSTRACT: Budd-Chiari syndrome (BCS) is a rare vascular disorder characterized by an obstruction of the hepatic venous outflow. Nodular regenerative hyperplasia (NRH) may develop as a result of an underlying autoimmune disease such as hepatic sarcoidosis. Only a few case reports have described cases with either NRH or hepatic sarcoidosis associated with BCS. We present a 42-year-old man presenting with BCS and signs of portal hypertension who was found to have an underlying pathological diagnosis of both hepatic sarcoidosis and NRH and who was successfully treated with a transjugular intrahepatic portosystemic shunt.